Peran Etika Bisnis dalam Memediasi Pengaruh Kecerdasan Emosional dan Inovasi Produk untuk Meningkatkan Daya Saing UMKM - Indira Oktavianti; Sudarmiatin Sudarmiatin; Ludi Wishnu (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This study aims to analyse the effect of Emotional Intelligence and Product Innovation on Increasing Competitiveness of MSMEs in East Java. business ethics as a mediating variable. Currently, businesses that have competitive are one of the factors that support the success of a business. Emotional intelligence is the ability possessed by MSME actors in developing their business policies, product innovation is identified as another factor that to influence the improvement of competitiveness for MSMEs. business ethics are considered to mediate the relationship between these variables, in order to strengthen the influence of emotional intelligence and product innovation on increasing the competitiveness of MSMEs. This research method uses a quantitative approach with a cross-sectional design. Respondent data collection to 72 MSME in East Java who the researcher's criteria. Data analysis using SEM The results showed that emotional intelligence and product innovation have a significant influence on increasing the competitiveness of MSMEs. Business ethics also proven to act as a mediating variable that strengthens the influence of the two independent variables on increasing the competitiveness of MSMEs. This research provides an important contribution to policy development for MSME players in terms of decision making by considering ethical behaviour practices for sustainable business.